Chronic macerated plaques over the genitalia in an elderly female: A diagnostic challenge - S Suvarna; Jacintha Martis; B Nandakishore; Ganesh H Kamath; Reshma G Kini (Wolters Kluwer Medknow Publications, 2017)
Extramammary Paget's disease (EMPD) is a rare dermatosis occurring in sites rich in apocrine glands, such as the vulva, anogenital region, and axilla. It can be subdivided into primary and secondary disease. An 84-year-old female presented with itchy, whitish, oozy raised lesions over the genitalia and groin since 2 years, associated with burning sensation. Examination revealed erythema, maceration and white oozy plaques over bilateral groin folds, perineum, and labia majora. She was treated as candidal intertrigo with secondary infection, with antibiotics and antifungals with minimal improvement. Routine blood investigations were within normal limits. Skin biopsy done from the vulva showed Paget cells in the lower two-thirds of the epidermis. She was diagnosed to have EMPD and referred to the oncosurgeon for further management. We present this case due to the rarity of its occurrence and to emphasize the high index of clinical suspicion required for chronic, macerated, erythematous plaques over the perineum, which do not respond to conventional treatment, in an elderly patient.